Co-transcriptional production of RNA–DNA hybrids for simultaneous release of multiple split functionalities. Issue 3 (3rd November 2013) - Afonin, Kirill A.; Desai, Ravi; Viard, Mathias; Kireeva, Maria L.; Bindewald, Eckart; Case, Christopher L.; Maciag, Anna E.; Kasprzak, Wojciech K.; Kim, Taejin; Sappe, Alison; Stepler, Marissa; KewalRamani, Vineet N.; et al.
Abstract: Control over the simultaneous delivery of different functionalities and their synchronized intracellular activation can greatly benefit the fields of RNA and DNA biomedical nanotechnologies and allow for the production of nanoparticles and various switching devices with controllable functions. We present a system of multiple split functionalities embedded in the cognate pairs of RNA–DNA hybrids which are programmed to recognize each other, re-associate and form a DNA duplex while also releasing the split RNA fragments which upon association regain their original functions. Simultaneous activation of three different functionalities (RNAi, Förster resonance energy transfer and RNA aptamer) confirmed by multiple in vitro and cell culture experiments prove the concept. To automate the design process, a novel computational tool that differentiates between the thermodynamic stabilities of RNA–RNA, RNA–DNA and DNA–DNA duplexes was developed. Moreover, here we demonstrate that besides being easily produced by annealing synthetic RNAs and DNAs, the individual hybrids carrying longer RNAs can be produced by RNA polymerase II-dependent transcription of single-stranded DNA templates.